LA PATERNIDAD: UNA MIRADA RETROSPECTIVA - Torres Velázquez, Laura Evelia (2023)
In the presence of the constant changes in the Spanish family, the roles of men and women have been modified. Perhaps these modifications have not taken over completely in the practical aspect but certainly in the ideological aspect, having as a result less precision in the daily tasks of men and women, and especially in the task of fatherhood. This study examines the perception that 18 Spanish males have about the paternity. The duty that males have today is to transform the model of acquired paternity, which demands essential changes in their masculine identity and paternal practice.